Reforming agricultural markets in Africa - Kherallah, Mylene; Delgado, Christopher L.; Gabre-Madhin, Eleni Zaude; Minot, Nicholas; Johnson, Michael E. (International Food Policy Research Institute, 2002)
Since the early 1980s, almost all African governments have embarked on economic reform programs to reduce state intervention in the economy and to allow markets to play a larger role. In the agricultural sector these programs were designed to eliminate price controls on agricultural commodities, disband or privatize state farms and state-owned enterprises, reduce the heavy taxation of agricultural exports, phase out subsidies on fertilizer and other inputs, and allow greater competition in agricultural markets. These measures have been highly controversial. Proponents argue that the reforms have improved market efficiency, reduced budget deficits, stimulated export production, and increased the share of the final price received by farmers. Opponents argue that the reforms have destabilized agricultural prices, widened the income distribution gap, and reduced access to low-cost inputs. Reforming Agricultural Markets in Africa by Mylène Kherallah, Christopher Delgado, Eleni Gabre-Madhin, Nicholas Minot, and Michael Johnson, published by The Johns Hopkins University Press for IFPRI, reviews the experience of the last 20 years. It evaluates the degree to which the reforms have actually been implemented, their impact on agricultural production and prices, and the net effect on the well-being of African households." --Author's Introduction.